2014
DOI: 10.1108/jcm-05-2014-0988
|View full text |Cite
|
Sign up to set email alerts
|

Spanning the gap: an examination of the factors leading to the green gap

Abstract: Spanning the gap: an examination of the factors leading to the green gap Mark Gleim Stephanie J. Lawson Article information:To cite this document: Mark Gleim Stephanie J. Lawson , (2014),"Spanning the gap: an examination of the factors leading to the green gap", Journal of Consumer Marketing, Vol. 31 Iss 6/7 pp. 503 -514 Permanent link to this document: http://dx. Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 64 publications
6
103
0
7
Order By: Relevance
“…A literature review on green purchase intention indicated that many studies have examined the antecedents of green purchase intentions, including environmental perceptions (Dagher and Itani, 2014), self-serving motives (Schuitema and de Groot, 2015), types of green claims (Chen and Lee, 2015), and perceived value and risk of green products (Koller et al, 2011;Chen and Chang, 2012;Wu et al, 2015). However, despite the green concern expressed in many studies, only 16% of people were estimated to act on green purchase behavior (Mahoney, 2011), and a green gap, the distance between the stated importance of protecting the environment and the actual behavior to help the environment, existed (Mahoney, 2011;Gleim and Lawson, 2014). Gleim and Lawson (2014) suggested that the green gap exists because of several reasons, of which price is the most common.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…A literature review on green purchase intention indicated that many studies have examined the antecedents of green purchase intentions, including environmental perceptions (Dagher and Itani, 2014), self-serving motives (Schuitema and de Groot, 2015), types of green claims (Chen and Lee, 2015), and perceived value and risk of green products (Koller et al, 2011;Chen and Chang, 2012;Wu et al, 2015). However, despite the green concern expressed in many studies, only 16% of people were estimated to act on green purchase behavior (Mahoney, 2011), and a green gap, the distance between the stated importance of protecting the environment and the actual behavior to help the environment, existed (Mahoney, 2011;Gleim and Lawson, 2014). Gleim and Lawson (2014) suggested that the green gap exists because of several reasons, of which price is the most common.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 96%
“…However, despite the green concern expressed in many studies, only 16% of people were estimated to act on green purchase behavior (Mahoney, 2011), and a green gap, the distance between the stated importance of protecting the environment and the actual behavior to help the environment, existed (Mahoney, 2011;Gleim and Lawson, 2014). Gleim and Lawson (2014) suggested that the green gap exists because of several reasons, of which price is the most common. This finding may correspond to the phenomenon that firms selling take-out beverages offer price discounts to encourage customers to bring their own cups.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 96%
“…In the present study, the researches described personal moral norm as "a norm in which a customer determines to adopt or not based on their own personal responsibility instead of social pressure or social norm. Gleim & Lawson (2014) is of the view that the actions of consumers also depend on their Journal of Sociological Research ISSN 1948-5468 2019 personal norms. According to Schwartz (1977) personal norms are at the individual level and it is about how a particular person feels as to what to do in a particular situation.…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%
“…Knowledge was found to be the one of the most studied variable; sixteen studies which taken for the present study examined consumers' knowledge and awareness of green products. Out of these fifteen studies, fourteen studies recognized that knowledge and awareness of green products positively influenced on consumer intention and adoption to green products (e.g., Gleim, 2014;Karunnayake & Wanninayake, 2015;Soon et al, 2013). Only one study reported that lack of knowledge on green products negatively influence on purchase intention.…”
Section: Environmental Knowledge and Awarenessmentioning
confidence: 99%
See 1 more Smart Citation